Impact of pandemics on humanitarian retailing operations: A voucher's case - Navid Mohamadi; Hataw Bakhishi; Sandra Transchel; Maria Besiou (Production and Operations Management, 2022)
In 2020, the world started a fight against a pandemic that has severely disrupted commercial and humanitarian supply chains. Humanitarian organizations (HOs), like the World Food Programme (WFP), adjusted their programs in order to manage this pandemic. One such program is cash and voucher assistance (CVA), which is used to bolster beneficiaries' freedom of choice regarding their consumption. In this vein, WFP supports local retailers to provide CVA to beneficiaries who do not have access to a functioning market. However, the operations of these stores can suffer from a very high transmission risk of COVID-19 unless preventive measures are put in place to reduce it. This paper discusses strategies that retailers and HOs can enact to maximize their service and dignity levels while minimizing transmission risk under a CVA program during a pandemic. We argue that HOs providing CVA programs can improve their assistance during a pandemic by implementing strategies that impact the retailing operations of their~retailers.
Keywords: 650; cash and vouchers assistance; competition; humanitarian operations; pandemics; retail operations; simulation